Effect of high-speed parameters on uncoated carbide tool in finish turning Titanium Ti-6Al-4V ELI - Sulaiman, Mohd Amri; Kasim, Mohd Shahir (Penerbit Universiti Kebangsaan Malaysia, 2014)

(untitled)
In this work, the Sandvik uncoated carbide insert, CNGG 120408-SGF-H13A was used as a cutting tool in high-speed turning of titanium alloy Ti-6Al-4V ELI (extra-low interstitial) with hardness of 32 HRC. Wear is one of the problems that cannot be avoided in machining process. Therefore, the objective of this paper was to investigate tool-wear behavior of various cutting-speed values (high-speed range) on the tool life of the cutting tools, especially in finishing titanium alloy. The experiments were performed under flooded coolant condition using water-based mineral-oil. The cutting speeds employed were 120, 170 and 220 m/min. The feed rate was constant at 0.2 mm/rev and the depth of cut was 0.4 mm. Based on the results, the highest cutting speed of 220 m/min caused the highest wear rate. By linking the machine operations and the tool life curves obtained using flank wear data, the wear behavior of uncoated carbide was described.